HRM ALGORITHMS AND VALUE CREATION THROUGH AI IN TRAINING AND DEVELOPMENT - IVANA, Diana (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
The purpose of this research study is to investigate the effect of HRM algorithms thorough Artificial Intelligence (AI) on small and medium-sized enterprises, with a specific focus on Learning and Development processes. Based on insights shared by technical and HR managers, this study shows that AI-driven HRM algorithms provide effective mechanisms for improving the efficiency of training sessions to cater learning interests while synchronizing it with business requirements. The results also suggest that although there is concern about AI replacing human teachers and the strategy of virtual classes, the potential benefits in changing the learning and development process makes it generally positive on deploying AI. In other words, AI could bring great hope of improving education/training and yet there are some limitations. JEL Classification: M12, M15, M54